Study of deep inelastic inclusive and diffractive scattering with the ZEUS forward plug calorimeter - Chekanov, S; Derrick, M; Magill, S; Miglioranzi, S; Musgrave, B; Repond, J; Yoshida, R; Mattingly, M; Pavel, N; Yagües Molina, A; Antonioli, P; Bari, G; et al. (2005)
Deep inelastic scattering and its diffractive component, ep → e′ γ* p → e′ X N, have been studied at HERA with the ZEUS detector using an integrated luminosity of 4.2 pb-1. The measurement covers a wide range in the γ* p c.m. energy W (37-245 GeV), photon virtuality Q2 (2.2-80 GeV2) and mass MX (0.28-35 GeV). The diffractive cross section for MX > 2 GeV rises strongly with W; the rise is steeper with increasing Q2. The latter observation excludes the description of diffractive deep inelastic scattering in terms of the exchange of a single pomeron. The ratio of diffractive to total cross section is constant as a function of W, in contradiction to the expectation of Regge phenomenology combined with a naive extension of the optical theorem to γ* p scattering. Above MX of 8 GeV, the ratio is flat with Q2, indicating a leading-twist behaviour of the diffractive cross section. The data are also presented in terms of the diffractive structure function, F2D(3)(β, xℙ, Q2), of the proton. For fixed β, the Q2 dependence of xℙF2D(3) changes with xℙ in violation of Regge factorisation. For fixed xℙ, xℙ F2D(3) rises as β → 0, the rise accelerating with increasing Q2. These positive scaling violations suggest substantial contributions of perturbative effects in the diffractive DIS cross section. © 2005 Elsevier B.V. All rights reserved.